ANALYSIS OF IM PACT OF MORPHOLOGICAL ATTRIBUTES ON JUMPING DISCIPLINES IN TRACK AND FIELD - Kemal Idrizović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In order to be able to influence as efficiently as possible on transformation of segments and sub-segments of psychosomatic status of a man, it is very important to know the structure of that space and relations in that structure. The basic problem of this research was finding and checking correlations of certain segments of morphologic space with results in athletic discipline of the long jump. The purpose of this paper was to determine an influence of predictive variable system (anthropometrical indicators) on criterion variable (result in the long jump), as well as to determine correlation of any predictive variable from the applied predictive system with criterion variable, in terms of determining participation of predictive in explanation of the results in a criterion.